Analisis Kesulitan Belajar Operasi Hitung Penjumlahan, Pengurangan, Perkalian Dan Pembagian Pada Siswa Kelas IV SD N Bugel Panjatan Kulon Progo - Danuri, Danuri; Ridho, Rizki Muhammad (Universitas Muhammadiyah Magelang, 2020)
Analysis of learning difficulties in mathematics is one of the important activities in order to determine the obstacles experienced during class learning. This research aims to analyze the difficulty of learning in the material operations of the addition, subtraction, multiplication and division in grade IV students at Bugel state elementary school, Panjatan, Kulon Progo, Yogyakarta. The research method used is a qualitative approach. This research was carried out in May 2020. From the social situation, there were grade IV students at state elementary school in Kepanewonan Panjatan, Kulon Progo Yogyakarta. The subjects in this study were grade IV students and teachers. Data collection used were observation, interview, and test techniques. The collected data were analyzed using the Miles and Huberman model data analysis which included data reduction, presentation, and drawing conclusions. Then the data validity test was done by triangulation of sources, and techniques. The results of the study on the arithmetic operations and operations reduction students did not have difficulty in understanding the material and calculating the matter of addition and subtraction. While in multiplication and division operations, there were still students who had difficulties.